School–Parent Association Partnership Management in Enhancing The Effectiveness of The Merdeka Curriculum Implementation: A Qualitative Study - Supriatin Supriatin; Heri Priyanto; Mukhammad Firmansyah; A Faizin (LPPM Universitas KH. A. Wahab Hasbullah, Jombang, Indonesia, 2026)
The implementation of the Merdeka Curriculum requires a supportive educational ecosystem in which collaboration between schools and parents plays a strategic role. This study aims to analyze how school–parent association partnership management enhances the effectiveness of Merdeka Curriculum implementation at Guslah 1, Bangil. Employing a qualitative approach with a case study design, the research involved key stakeholders, including the school principal, vice principal for curriculum, teachers, parent association or school committee leaders, and actively involved parents. Data were collected through in-depth interviews, participant observation, and document analysis, and analyzed using an interactive model consisting of data condensation, data display, and conclusion drawing, supported by triangulation techniques to ensure credibility. The findings reveal that effective partnership management functions as a systemic ecosystem that facilitates shared understanding, acceptance, and consistent curriculum implementation. At the planning stage, collaborative and structured coordination ensures role clarity, program alignment, and transparent communication. During implementation, organized parental involvement supports learning continuity, character development, student self-development, and the legitimacy of school programs. Furthermore, collaborative monitoring and evaluation strengthen accountability, improve student engagement, and increase parental acceptance of curriculum changes. The study concludes that POAC-based (Planning, Organizing, Actuating, and Controlling) partnership management at Guslah 1, Bangil represents a professional, participatory, and adaptive governance model that integrates family engagement and local values of gotong royong, thereby contributing significantly to the contextual and sustainable implementation of the Merdeka Curriculum.